2014
DOI: 10.1038/ncomms5716
|View full text |Cite
|
Sign up to set email alerts
|

A general and scalable synthesis approach to porous graphene

Abstract: Porous graphene, which features nano-scaled pores on the sheets, is mostly investigated by computational studies. The pores on the graphene sheets may contribute to the improved mass transfer and may show potential applications in many fields. To date, the preparation of porous graphene includes chemical bottom-up approach via the aryl-aryl coupling reaction and physical preparation by high-energy techniques, and is generally conducted on substrates with limited yields. Here we show a general and scalable synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(111 citation statements)
references
References 47 publications
1
109
1
Order By: Relevance
“…S3, N atoms were doped in graphene basal plane in three configurations. They were pyrrolic N (N-5) at binding energy of 399.8 eV, pyridine N (N-6) at 398.2 eV and quaternary N (N-Q) at 401.3 eV [39,52]. Besides improving the wettability of electrode, the N-6 contributes the pseudocapacitance because of its high binding energy with K + , allowing more K + to be accumulated on the electrode surface [53].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S3, N atoms were doped in graphene basal plane in three configurations. They were pyrrolic N (N-5) at binding energy of 399.8 eV, pyridine N (N-6) at 398.2 eV and quaternary N (N-Q) at 401.3 eV [39,52]. Besides improving the wettability of electrode, the N-6 contributes the pseudocapacitance because of its high binding energy with K + , allowing more K + to be accumulated on the electrode surface [53].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, recent achievements have also demonstrated that the existence of in-plane nanopores not only improves the electrode utilization efficiency for charge storage, but also promotes the diffusion of electrolyte ion across the graphene 2D basal plane [34,35]. Among various methods, chemical activation of graphene with diverse activation agents, including KOH [36][37][38], metal oxides [32,39], KMnO 4 [40] and concentrated HNO 3 [41] have been successfully utilized to oxidize carbon atoms to produce in-plane nanopores. However, construction of these 2D porous graphene sheets into a macroscopically 3D architecture for practical applications still remains a great challenge [32,42].…”
Section: Introductionmentioning
confidence: 98%
“…The experimental synthesis of nanoporous graphene has become a subject of tremendous interest [101][102][103]. Achieving highly uniform, subnanometer pores in large-scale sheets of graphene is arguably the most important outstanding goal for the field of NPG membranes, and O'Hern et al have recently produced pores with diameters of (0.40 ± 0.24) nm and densities exceeding 1 × 10 12 cm −2 , while retaining structural integrity of the graphene [8].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…The above results reveal that some energy is needed to initiate the reaction between Ni and graphene, which matches well with the research result of Ramasse et al [22] During this reaction, the OM or POM species was decomposed and reduced into metal oxide, metal and/or metal carbide compounds, and the carbon atoms on the graphene sheets were partially oxidized into carbon monoxide and/or dioxide. [25] Compared with OM or POM, we employed acetate or nitrate as a more simple reaction system. More importantly, in order to demonstrate that the pores are formed due to the local oxidation of the metallic ad-atoms followed by C-atom dissociation through C-O formation, [22] the tail gas during the reaction was monitored in situ.…”
Section: Electrochemical Measurementmentioning
confidence: 99%